A case study exploring FM components for elderly in care and attention homes using post occupancy evaluation. Issue 11 (4th August 2014) - Leung, Mei-yung; Yu, Jingyu; Dongyu, Chen; Yuan, Ting
Abstract : Purpose: – The paper aims to investigate the key components of facilities management (FM) in care and attention (C & A) homes from the end users' perspective based on a post-occupancy evaluation method. Hong Kong is a rapidly ageing society. Elderly population may reach 24.3 per cent in the next 20 years, causing an increase in the demand for care services. Therefore, it is necessary to provide sufficient and satisfactory residential C & A homes with appropriate facilities for our elderly. Design/methodology/approach: – To collect subjective data from end users, a questionnaire survey was conducted in 119 respondents consisting of both elderly residents and staff of the C & A homes. To further understand the actual situations, site measurements were also used to collect the objective data from the representative homes. Findings: – The results indicate that three aspects of key FM components, namely, architect, building services and supporting, all have significant relationships with the overall satisfaction. The site measurements further revealed the actual environment of the seven C & A homes, especially the contrasts between homes with highest scores (Homes E and F) and lowest scores (B and D). Practical implications: – To provide a clear picture to the government and construction professionals, a number of practical recommendations were proposed, such as sufficient space with single or couple bedrooms, sufficient corridor width for two people in wheelchairs and white or pink as the colour scheme in architectural aspect; sufficient lighting, central air conditioning system and adequate quantities of natural fresh air in the building service aspect; and frequently updated menus, door lock and CCTV system for supporting facilities. Originality/value: – This paper applied site measurement on the representative homes to cross-check the quantitative results. The findings of this study can assist architects and facilities managers in C & A homes to improve FM services during the design and operational stages for improving the satisfaction levels of elderly residents.